KEWENANGAN DAERAH KABUPATEN DALAM PENGAWASAN PERTAMBANGAN RAKYAT DI DAERAH - Anastasia Pricillia Wibowo (Jurnal HUKUM BISNIS, 2023)
This study aims to determine the role of local governments in supervising mining activities. Since the enactment of Law no. 3 of 2020 concerning Mineral and Coal Mining, the existence of community mining from the aspect of licensing, supervision, guidance, to environmental management is increasingly making it difficult for small communities, while the authority of district/city governments in issuing mining permits based on Law Number 23 of 2014 concerning Regional Government is divided between the government and the provincial government. The authority to issue mining permits based on the concept of regional autonomy is more appropriate if it is owned by the district/city government. Because it is the district/city government that knows more clearly the area. District/city local governments who know that a mining permit can be granted to a person and/or business entity or not, because the district/city government is easier to observe in the field, because the distance is not far. The purpose of this research is to find out how far the state is in favor of the existence of smallholder mining after the new regulation changes. The benefit side in terms of legal policies in order to strengthen the legal position of people's mining. This research method uses a normative method and then analyzed qualitatively with a Legislative and Conceptual approach. Then analyzed qualitatively.Keywords: regional authority, local government, mining supervision